2007
DOI: 10.1016/j.neulet.2007.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine reward in the monogamous prairie vole

Abstract: Recent studies have shown that the neural regulation of pair bonding in the monogamous prairie vole (Microtus ochrogaster) is similar to that of drug seeking in more traditional laboratory rodents. Therefore, strong interactions between social behavior and drug reward can be expected. Here, we established the prairie vole as a model for drug studies by demonstrating robust amphetamineinduced conditioned place preferences in this species. For both males and females, the effects of amphetamine were dose-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 62 publications
(68 reference statements)
5
24
0
Order By: Relevance
“…In this study, we replicate our previous finding that AMPH exposure induces CPP in male prairie voles (22) and demonstrate that D1R activation in the NAcc is necessary for this behavior, a result consistent with studies in other rodent species (28). This finding, together with earlier studies, suggests that distinct DAergic mechanisms in the NAcc regulate AMPH-and partner-motivated behaviors: AMPH-motivated behavior (CPP) is mediated by D1R, whereas partner-motivated behavior (partner preferences) is facilitated by D2R activation and inhibited by D1R activation within the NAcc (13)(14)(15).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this study, we replicate our previous finding that AMPH exposure induces CPP in male prairie voles (22) and demonstrate that D1R activation in the NAcc is necessary for this behavior, a result consistent with studies in other rodent species (28). This finding, together with earlier studies, suggests that distinct DAergic mechanisms in the NAcc regulate AMPH-and partner-motivated behaviors: AMPH-motivated behavior (CPP) is mediated by D1R, whereas partner-motivated behavior (partner preferences) is facilitated by D2R activation and inhibited by D1R activation within the NAcc (13)(14)(15).…”
Section: Discussionsupporting
confidence: 91%
“…The neurobiology of such social attachment, specifically pair bonding between adults, has been extensively studied in the prairie vole (10)(11)(12), and recently, this species has been established as a viable model to examine the motivational value of AMPH (22). Moreover, both pair bond formation and AMPH reinforcement are mediated, at least in part, by DA transmission within the NAcc (14,15,23).…”
mentioning
confidence: 99%
“…The following behavioral patterns of the resident were subsequently quantified: the frequency of attacks, bites, chases, defensive/offensive upright postures, offensive sniffs, threats, and retaliatory attacks, and calculated as a composite score (aggression frequency) (26), as well as the duration of affiliative side-by-side physical contact (28). Procedures for stereotaxical cannulation, site-specificinfusions, and AMPH injections were described previously (25,51). Bilateral guide cannulae were stereotaxically implanted and aimed into the AH (coordinates from bregma: posterior 0.55 mm, lateral Ϯ 0.75 mm, ventral 5.9 mm).…”
Section: Methodsmentioning
confidence: 99%
“…In both species, social reward and drug reward show striking parallels at the behavioral and neurobiological levels (5-9). Prairie voles are now being used to explore the interactions between social relationships and drug abuse (10)(11)(12)(13)(14)(15)(16)(17)(18)(19).We previously demonstrated that prairie voles voluntarily selfadminister substantial amounts of alcohol (ethanol) and can influence the drinking patterns of a social partner (16)(17)(18)(19), similar to social drinking in humans (20). Because alcohol is known to influence social bonds in humans (21-24), we asked here whether alcohol consumption can affect the formation of adult social attachments in prairie voles.…”
mentioning
confidence: 99%
“…In both species, social reward and drug reward show striking parallels at the behavioral and neurobiological levels (5-9). Prairie voles are now being used to explore the interactions between social relationships and drug abuse (10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
mentioning
confidence: 99%